1964
DOI: 10.1524/ract.1964.2.4.204
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption and Sedimentation of Clean, Carrier-Free, Yttrium Solutions

Abstract: Zusammenfassung BesumeExperiments on the adsorption and Sedimentation of yttrium solutions have been carried out with solutions containing minimal suspended matter. It has been shown that such clean solutions of 'carrierfree' yttrium can be kept in polystyrene vessels, even at pH = 8 or more, with no Sedimentation taking place, and only a small amount of adsorption on to the vessel walls. It has also been shown that addition of 'Analar' water to such solutions converts the yttrium to a centrifugable form. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1966
1966
1982
1982

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Samples were re-immersed for further times as required. Removal and replacement of the samples did not significantly affect the sorption isotherms, and it was found also that adsorption on the vessel-walls was always less than 1 per cent (this agrees with the observations of MELLISH et al [9]). …”
Section: Introductionsupporting
confidence: 91%
“…Samples were re-immersed for further times as required. Removal and replacement of the samples did not significantly affect the sorption isotherms, and it was found also that adsorption on the vessel-walls was always less than 1 per cent (this agrees with the observations of MELLISH et al [9]). …”
Section: Introductionsupporting
confidence: 91%
“…76 The molecular species of 7 Be formed in water surrounding the accelerator tunnel will be in the form of a strongly hydrolyzed ion, similar to the radiocolloid described by Mellish et al 78 In particular, 7 Be has been recognized as being a species which is very strongly absorbed onto surfaces from carrier-free solution; indeed, in solution in which the Be content is considerably less than the solubility product for the hydrolyzed cation, separations of carrier-free 7 Be may be made by a simple filtration. 79 -80 Therefore, it would follow that this known sorption of tracer beryllium might result in holdup in the wet rock for periods sufficient to allow significant decay to occur and to reduce concentrations in ground water due to low leach rates from the regions of greatest yields from around the accelerator ring.…”
Section: IIImentioning
confidence: 90%
“…Indeed, this double layer was proved to exist on the surface of teflon at pa values higher than 3 [20], However, it has been shown that its capacity is very small. Some authors have also pointed out the possibility of explaining adsorption phenomena by the ion exchange properties of either foreign impurities in the adsorbent or of some groups formed by a surface oxidation of polymer [3,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…6 it also follows that indifferent electrolytes strongly affect the adsorption kinetics, probably due to their influence on the formation of adsorbable gold species. One might suggest that such electrolytes might either desorb the gold traces from the colloidal impurities, ever present in solution [22,23], or affect the equilibrium between various gold species due to the change in ionic strength of the solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation